Optimization of Chlorogenic Acid in Ethanol Extracts from Elderberry Flowers (Sambucus nigra L.) under Different Conditions: Response Surface Methodology - Maciej Oziembłowski; Agnieszka Nawirska-Olszańska; Damian Maksimowski (Applied Sciences, 2023)
The characteristics of elderberries and their flowers as well as selected properties of chlorogenic acid related to phenolic compounds are described. The aim of this study was to optimize the content of chlorogenic acid in ethanol extracts of elderberry flowers using the response surface methodology (RSM). The experiment was carried out with four research variants: fresh raw material treated with warm ethanol (50 °C) or cold ethanol (25 °C) and the same procedure for raw material that was frozen for a month and then dried. For each variant, nine methods of obtaining extracts were prepared using three different ethanol concentrations by volume (40, 68 or 95%) and three different extraction times (7, 20 or 30 days). Higher contents of chlorogenic acid were found in variants treated with warm ethanol (106.3 to 384.8 µg/cm3) in comparison to the samples treated with cold ethanol (60.77 to 298.3 µg/cm3). Optimization models of the response surface showed that with small losses of efficiency, the extraction process can be carried out for up to 20 days (instead of 30) with the use of ethanol with a concentration of approx. 68% (instead of 95%). The optimization of the efficiency of technological processes in the processing of herbs can be supported by the use of the response surface methodology.